2012
DOI: 10.1021/nl3005385
|View full text |Cite
|
Sign up to set email alerts
|

A Close Look at Proteins: Submolecular Resolution of Two- and Three-Dimensionally Folded Cytochrome c at Surfaces

Abstract: Imaging of individual protein molecules at the single amino acid level has so far not been possible due to the incompatibility of proteins with the vacuum environment necessary for high-resolution scanning probe microscopy. Here we demonstrate electrospray ion beam deposition of selectively folded and unfolded cytochrome c protein ions on atomically defined solid surfaces in ultrahigh vacuum (10(-10) mbar) and achieve unprecedented resolution with scanning tunneling microscopy. On the surface folded proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 56 publications
(112 reference statements)
4
129
0
2
Order By: Relevance
“…The spatial resolution of Fig. 4b is comparable to that of the recently reported STM image of cytochrome c. 39 The cytochrome c was carefully adsorbed on metal surfaces by electrospray ion beam deposition, and STM imaging was conducted in an ultrahigh vacuum condition. In the present study, the sample peptide was adsorbed simply by spin-coating and observed in an ambient condition; nevertheless, the similar resolution was achieved for 1GBP.…”
Section: Resultssupporting
confidence: 72%
“…The spatial resolution of Fig. 4b is comparable to that of the recently reported STM image of cytochrome c. 39 The cytochrome c was carefully adsorbed on metal surfaces by electrospray ion beam deposition, and STM imaging was conducted in an ultrahigh vacuum condition. In the present study, the sample peptide was adsorbed simply by spin-coating and observed in an ambient condition; nevertheless, the similar resolution was achieved for 1GBP.…”
Section: Resultssupporting
confidence: 72%
“…18,19 However, AFM is unable to resolve the structure of the peptide chains at the desired level of detail. Moreover, it is likely that the drying process will affect the structure of the peptide assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…[38] In these studies, rigid component molecules were usually employed to build polymers of different dimensions, whereas increasing attention has been given to the adsorption and on-surface synthesis of much larger and more flexible species. [39][40][41][42] The Schiff base reaction has been widely applied in dynamic covalent chemistry, [43,44] and it has also been investigated both under UHV and ambient conditions by means of scanning tunneling microscopy (STM). [23][24][25][32][33][34][35] The reactions, particularly those that result in small-molecule imine compounds, can proceed under room temperature, [32,43] whereas for the preparation of high-quality surface 2D polymers, mild heating is normally necessary.…”
Section: Introductionmentioning
confidence: 99%